An exploration of clinically meaningful definitions of cough bouts - Kimberley J. Holt; Rachel J. Dockry; Kevin McGuinness; Emma Barrett; Jaclyn A. Smith (ERJ Open Research)
Rationale The measurement of cough frequency is widely used in clinical trials, typically expressed as the number of explosive cough sounds per hour. However, this measure does not capture the clustering of coughs into bouts. Coughing bouts contribute to perceived cough severity and the physical complications of coughing, but an agreed standard definition of cough bouts is lacking. The objectives of the present study were to explore the impact of different definitions of cough bouts on the parameters generated, their relationships with reported cough severity and influence of age and gender in refractory chronic cough (RCC). Methods We analysed 24-h acoustic recordings and concurrent cough severity visual analogue scales from 91 RCC patients (62% female, median (interquartile range) age 60.0 (54–67.0) years). A custom-built algorithm calculated cough bouts, defined by the intervals between explosive cough sounds. Bouts defined by inter-cough intervals from ≤0.5 to ≤10 s (0.5 s increments) were explored, and parameters including number of bouts, median/maximum bout length and total bout duration calculated. Measurements and main results Using inter-cough intervals of >3 s to define cough bouts made little difference to cough bout parameters. Correlations between cough severity and bout parameters were weak but most likely to be significant when single coughs were removed. Cough-free time/total time spent coughing tended to have more influence on cough severity than the average cough bout length, irrespective of the interval used. Conclusion These analyses favour definitions of cough bouts utilising inter-cough intervals of ≤3 s and the exclusion of single coughs from cough bout analysis.